2014
DOI: 10.1161/hypertensionaha.114.03738
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Blockade Improves Insulin Sensitivity in Obese Subjects

Abstract: Obesity is an important risk factor for the development of insulin resistance. Initial compensatory mechanisms include an increase in insulin levels, which are thought to induce sympathetic activation in an attempt to restore energy balance. We have previously shown, however, that sympathetic activity has no beneficial effect on resting energy expenditure in obesity. On the contrary, we hypothesize that sympathetic activation contributes to insulin resistance. To test this hypothesis, we determined insulin sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 50 publications
1
36
0
1
Order By: Relevance
“…The P values were generated by Mann-Whitney U-test. agreement as to whether LF SBP reflects sympathetic modulation of vascular tone (18,39,40,49), we have previously shown that LF SBP is increased in obese hypertensives (19,20,52), decreased in patients with pure autonomic failure, virtually abolished by autonomic ganglionic blockade (10,20,52), and was also greatly reduced in the patients with DBH deficiency included in this study. Furthermore, during orthostatic stress and the Valsalva maneuver, lean POTS had excessive HR responses, and higher BP and upright plasma norepinephrine levels, indicating recurrent episodes of excessive sympathetic activation whenever patients stood.…”
Section: Discussionsupporting
confidence: 52%
“…The P values were generated by Mann-Whitney U-test. agreement as to whether LF SBP reflects sympathetic modulation of vascular tone (18,39,40,49), we have previously shown that LF SBP is increased in obese hypertensives (19,20,52), decreased in patients with pure autonomic failure, virtually abolished by autonomic ganglionic blockade (10,20,52), and was also greatly reduced in the patients with DBH deficiency included in this study. Furthermore, during orthostatic stress and the Valsalva maneuver, lean POTS had excessive HR responses, and higher BP and upright plasma norepinephrine levels, indicating recurrent episodes of excessive sympathetic activation whenever patients stood.…”
Section: Discussionsupporting
confidence: 52%
“…An inverse relationship between heart rate and insulin sensitivity, as assessed by an intravenous glucose tolerance test, was reported in the IRAS cohort (23). Furthermore, a recent study demonstrated that pharmacological blockade of the sympathetic system improved insulin sensitivity in obese insulin-resistant patients, which supports a direct influence of the autonomic nervous system on insulinmediated glucose utilization in humans (25).…”
Section: Discussionmentioning
confidence: 67%
“…55,56 Thus, these observations also provide a pathophysiological neurogenic mechanism by which a sustained increase in daytime central sympathetic outflow, induced by chronically disrupted sleep, could initiate and maintain hypertension 4,47 or insulin resistance. 57,58 The principal limitations to this work are its focus on generally nonsleepy, nonobese adults free of potentially confounding comorbidities, with few, despite selfprofessed normalcy, having an AHI <5 events/h (Figure), plus the correlational nature of these analyses, not yet replicated in an independent data set or re-evaluated after a sleep-consolidating intervention without direct autonomic effect. Studies involving a broader population or evaluating the impact of such interventions represent important future research steps toward translating the present findings into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Por consiguiente, estas observaciones también proporcionan un mecanismo fisiopatológico neurógeno por el que un aumento sostenido del flujo simpático central diurno, inducido por alteración crónica del sueño, podría inicial y mantener la hipertensión 4,47 o la resistencia a la insulina. 57,58 Las principales limitaciones de este trabajo son que se centra en adultos no obesos, generalmente no somnolientos sin enfermedades concomitantes que actúen como posibles factores de confusión, que tienen un IAH <5 episodios/h (Figura), más el carácter correlativo de estos análisis, todavía no reproducidos en un conjunto de datos independientes ni revaluados después de una intervención de consolidación del sueño sin efecto autónomo directo. Estudios que incorporen a una población más amplia o que evalúen la repercusión de estas intervenciones representan futuros pasos de investigación importantes para traducir los presentes hallazgos a la práctica clínica.…”
Section: Discussionunclassified